Pretreatment CT and 18F‐FDG PET‐based radiomic model predicting pathological complete response and loco‐regional control following neoadjuvant chemoradiation in oesophageal cancer. Issue 1 (1st December 2020) - Rishi, Anupam; Zhang, Geoffrey G; Yuan, Zhigang; Sim, Austin J; Song, Ethan Y; Moros, Eduardo G; Tomaszewski, Michal R; Latifi, Kujtim; Pimiento, Jose M; Fontaine, Jacques‐Pierre; Mehta, Rutika; Harrison, Louis B; et al.
Abstract: Introduction: To develop a radiomic‐based model to predict pathological complete response (pCR) and outcome following neoadjuvant chemoradiotherapy (NACRT) in oesophageal cancer. Methods: We analysed 68 patients with oesophageal cancer treated with NACRT followed by esophagectomy, who had staging 18F‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography (PET) and computed tomography (CT) scans performed at our institution. An in‐house data‐chjmirocterization algorithm was used to extract 3D‐radiomic features from the segmented primary disease. Prediction models were constructed and internally validated. Composite feature, F c  =  α  *  F PET  + (1 −  α ) *  F CT, 0 ≤  α  ≤ 1, was constructed for each corresponding CT and PET feature. Loco‐regional control (LRC), recurrence‐free survival (RFS), metastasis‐free survival (MFS) and overall survival (OS) were estimated by Kaplan–Meier analysis, and compared using log‐rank test. Results: Median follow‐up was 59 months. pCR was achieved in 34 (50%) patients. Five‐year RFS, LRC, MFS and OS were 67.1%, 88.5%, 75.6% and 57.6%, respectively. Tumour Regression Grade (TRG) 0–1 indicative of complete response or minimal residual disease was significantly associated with improved 5‐year LRC [93.7% vs 71.8%; P  = 0.020; HR 0.19, 95% CI 0.04–0.85]. Four sepjmirote pCR predictive models were built for CT alone, PET alone, CT+PET and composite. CT, PET and CT+PET models had AUC 0.73 ± 0.08, 0.66 ± 0.08 and 0.77 ± 0.07, respectively. The composite model resulted in an improvement of pCR predicting power with AUC 0.87 ± 0.06. Stratifying patients with a low versus high radiomic score showed clinically relevant improvement in 5‐year LRC favouring low‐score group (91.1% vs. 80%, 95% CI 0.09–1.77, P  = 0.2). Conclusion: The composite CT/PET radiomics model was highly predictive of pCR following NACRT. Validation in larger data sets is warranted to determine whether the model can predict clinical outcomes.